Feasibility study for green energy island : final report, Vol. - Azhaili, Baharun; Wan Azlan, Bin Wan Zainal Abidin; Kismet, Anak Hong Ping; Rohaida, Affandi; Hazrul, Mohamad Basri; Abg Mohd Nizam, Abg Kamaruddin; Ting, Sim Nee (Universiti Malaysia Sarawak, (UNIMAS), 2013)
This report consists of narrowing down more than 200 off grid sites based on the report by Kementerian Kemajuan Luar Bandar dan Wilayah (KKLW), Sarawak Energy Berhad (SEB) and Jabatan Kerja Raya (JKR) Sarawak to ten (10) sites that may have the potential for the GEI project implementation. The site investigations are carried out through rigorous and extensive site visits over eight (8) months period. Details of these site studies are presented in this report, covering the background of the selected sites, demographic data and technical data that includes hydrological data and load demand analysis.